Evaluation Of The Impact Of The Policy Implementation Of The Average Effective Tax Rate In Government Regulation No 58 Of 2023 - Chandra, Jeffry Setiady; Sari, Dahlia (E-Jurnal Akuntansi; Vol 35 No 3 (2025)DO - 10.24843/EJA.2025.v35.i03.p13, 2025)
This research aims to analyze the Average Effective Rate (TER) policy applied to the calculation of individual taxpayer employees, in accordance with Government Regulation Number 58 of 2023. The analysis assesses this policy from the perspective of employer taxpayers as tax withholders and individual employee taxpayers as those subject to withholding, based on the criteria of The Four Maxims: fairness, legal certainty, simplicity, and economic benefits. The analysis method used in this study is a descriptive qualitative case study. The research object is PT B, a company in the fashion industry employing approximately 800 people. The research methodology applies a triangulation method by utilizing primary data collection, literature studies, and secondary data. Primary data collection was conducted through questionnaires distributed to individual employee taxpayers and interviews with PT B's Accounting and Tax Manager, tax consultants, and government representatives from the Directorate General of Taxes (DJP) and the Fiscal Policy Agency (BKF). The research findings indicate that the effective rate policy adheres to the principles of fairness, legal certainty, simplicity, and economic benefits. Furthermore, analysis of information gathered from the respondents reveals that this policy encourages compliance with the reporting of Monthly Income Tax Article 21 (PPh 21) for employer taxpayers as withholders. However, compliance with the Annual Tax Return reporting for individual employee taxpayers cannot yet be analyzed, as the policy has not been in effect for a full year. Therefore, active involvement from the DJP is required to socialize the implementation of this policy, ensuring that it promotes compliance with Annual Tax Return reporting for individual employee taxpayers. Keywords: Average Efektif Rate (TER), The Four Maxims, policy evaluation, Article 21 Income Tax, Individual Employee Taxpayers.